2006
DOI: 10.3852/mycologia.98.6.1041
|View full text |Cite
|
Sign up to set email alerts
|

A multigene phylogeny of the Dothideomycetes using four nuclear loci

Abstract: We present an expanded multigene phylogeny of the Dothideomycetes. The final data matrix consisted of four loci (nuc SSU rDNA, nuc LSU rDNA, TEF1, RPB2) for 96 taxa, representing five of the seven orders in the current classification of Dothideomycetes and several outgroup taxa representative of the major clades in the Pezizomycotina. The resulting phylogeny differentiated two main dothideomycete lineages comprising the pseudoparaphysate Pleosporales and aparaphysate Dothideales. We propose the subclasses Pleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(66 citation statements)
references
References 40 publications
4
61
0
1
Order By: Relevance
“…CO27-5 v1.0 (Wu et al 2017), Neurospora crassa OR74A v2.0 (Galagan et al 2003), Lecythophora sp. AK0013 v1.0 (Damm et al 2010; U’Ren et al 2012), Botryosphaeria dothidea (Slippers et al 2004; Desprez-Loustau et al 2006; Schoch et al 2006; Slippers and Wingfield 2007; Piškur et al 2011), Fusarium oxysporum sp. lycopersici 4287 v2 (Ma et al 2010) with available annotated genomes were retrieved from the JGI (Joint Genome Institute) MycoCosm database.…”
Section: Methodsmentioning
confidence: 99%
“…CO27-5 v1.0 (Wu et al 2017), Neurospora crassa OR74A v2.0 (Galagan et al 2003), Lecythophora sp. AK0013 v1.0 (Damm et al 2010; U’Ren et al 2012), Botryosphaeria dothidea (Slippers et al 2004; Desprez-Loustau et al 2006; Schoch et al 2006; Slippers and Wingfield 2007; Piškur et al 2011), Fusarium oxysporum sp. lycopersici 4287 v2 (Ma et al 2010) with available annotated genomes were retrieved from the JGI (Joint Genome Institute) MycoCosm database.…”
Section: Methodsmentioning
confidence: 99%
“…Members of Phaeosphaeriaceae can be endophytic, epiphytic, saprobic, or pathogenic on plants with many species and their asexual morphs causing serious diseases of crops worldwide (Shoemaker & Babcock 1989, Schoch et al 2006, Hyde et al 2013. Barr (1979) introduced Phaeosphaeriaceae with Phaeosphaeria as the type genus and described the family as saprobic, pathogenic or hyperparasitic.…”
Section: Introductionmentioning
confidence: 99%
“…Phaeosphaeriaceae is a large and important family of Pleosporales, in the suborder Pleosporineae, Dothideomycetes (Câmara et al 2002, Kodsueb et al 2006, Schoch et al 2006, Gruyter et al 2010, Hyde et al 2013. Members of Phaeosphaeriaceae can be endophytic, epiphytic, saprobic, or pathogenic on plants with many species and their asexual morphs causing serious diseases of crops worldwide (Shoemaker & Babcock 1989, Schoch et al 2006, Hyde et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbsch & Lindemuth (2001) used LSU and SSU gene data to analyze the major lineages of Dothideomycetes in which the Myriangium species were included in the order Myriangiales. Schoch et al (2006) used M. duriaei and four Elsinoe spp. in their phylogenetic analyses and found that these Elsinoe species belong to a different family, Elsinoaceae.…”
Section: Taxonomymentioning
confidence: 99%